Design of an Android-based Prayer Guidance Application Based on Al-Quran and Sunnah - Novi Hendri Adi; Abdul Somad; Farid Kassimov; Abzal Kuanyshuly (Journal of Computer-based Instructional Media, 2023)
Prayer is the cornerstone of religion, and it is an obligation for Muslims who have reached the age of accountability. Prayer is a great act of worship, because it is a direct command from Allah ta'ala to Muslims, whose command was directly received by the Messenger of Allah (peace and blessings of Allah be upon him) without the mediation of Gabriel (peace be upon him) at Sidratul Muntaha on the occasion of Isra' and Mi'raj. Prayer is the first thing that will be judged on the Day of Judgement, as the Messenger of Allah (peace and blessings of Allah be upon him) said: "The first thing that will be judged of a slave on the Day of Judgement is prayer. If his prayer is good, all his deeds will be good. If the prayer is bad then all his deeds will be bad". Education or teaching prayer to children is so important that even Rosulullah sholallahu alaihi wassalam has firmly prescribed that prayer education begins at an early age, that is, before they reach the age of puberty. Even when children are seven years old, they have been ordered to pray. This application is multimedia-based to be more interesting and easily understood by children in learning prayers because there are images, sounds and videos in it.